1999
DOI: 10.2500/105065899781389803
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Nitric Oxide: A Comparison of Measurement Techniques

Abstract: Nasal nitric oxide measurement may be a surrogate marker of upper airway inflammation. There is, however, no standardized measurement technique; and this led us to examine measurement techniques for acceptability and reproducibility. In five subjects we examined the flow dependence of nasal NO. In 13 healthy volunteers, nasal NO was measured on-line by five methods: 1) Tidal nasal and oral breathing: NO sampling during exclusive nasal followed by exclusive oral tidal breathing; 2) Fixed flow exhalation: NO sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
69
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 26 publications
1
69
0
1
Order By: Relevance
“…Nasal (supravelum) measurement techniques have been extensively discussed and consensus has been reached on what methods should be used [14,16]. However, no clearcut explanations of what is being measured and why different measurements yield different NO outputs at different flow rates have been put forward [15,18,19]. In the present study healthy young subjects performing exhalations in a highly reproducible way were examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nasal (supravelum) measurement techniques have been extensively discussed and consensus has been reached on what methods should be used [14,16]. However, no clearcut explanations of what is being measured and why different measurements yield different NO outputs at different flow rates have been put forward [15,18,19]. In the present study healthy young subjects performing exhalations in a highly reproducible way were examined.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it could be argued that a nasal exhalation better reflects normal physiological conditions for transnasal airflow than the aspiration/insufflation methods. The single-breath method is widely accepted for oral exhalations and the nose-mask was well tolerated [19] and easily adapted to the setup for oral measurements.…”
Section: Discussionmentioning
confidence: 99%
“…By this means NO is thought to modulate nasal vascular conductance and nasal cavity volume, which are correlated to the nasal airway resistance [16,17]. It should be noted however, that recent investigations, using high flow rate insufflation, contradict the existence of such a relationship [31,32]. The difference in these results is thought to be due to underestimation of measured NO outputs as low flows were used instead of higher and probably more physiological transnasal airflows [33].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the relatively high levels of inhaled NO used in these studies, clinical effects have been shown using levels as low as 100-150 parts per billion (ppb) in acute respiratory failure and ARDS [13][14][15]. The level of NO in the nasal cavity varies with the measurement method [16] but often exceeds 100 ppb. Autoinhalation of nasal NO occurs and has physiological effects as an airborne messenger [3,17].…”
mentioning
confidence: 99%